Financial Attitude and Locus of Control Toward Financial Management Practices - Lestari, Emi; Yap, Nonni; Choiri, Choiri (International Conference On Economics Business Management And Accounting (ICOEMA), 2025)
The purpose of this study is to analyze and synthesize a theory that explains the relationship between financial attitude, locus of control and financial management practices. This study uses a qualitative approach with the literature review method, which is an approach that examines and synthesizes previous research by selecting relevant literature, analyzing and solving and interpreting the synthesis of literature. This study examines 50 articles sourced from the Google Scholar database, Mandeley Search, Emerald Insight and Harzing's Publish or Pherish. This study presents the theoretical basis, other explanatory variables and research results from previous literature. Theories that underlie it include planned behavior theory. The synthesis of the research results shows that good and reliable financial attitude and locus of control have a significant impact on Financial Management Practices. A positive financial attitude encourages individuals to manage their finances better, including planning, controlling, and making financial decisions.